Artemis Fowl : the lost colony - Colfer, Eoin (Colfer, Eoin. Artemis Fowl, 2018)
When demons begin appearing on Earth unpredictably, foreshadowing a cataclysmic breakdown of their magic, Artemis and his friends face a new foe--a twelve-year-old girl whose intellect just might match Artemis's own--as they try to prevent catastrophe.